A Critique on the Book Etiology of Iran’s Underdevelopment - Iraj Varfinezhad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The issue of underdevelopment has always been one of the research attractions for researchers. Underdevelopment has been one of the main concerns of Iranian reformers and thinkers, at least since the early Qajar period, which has led to various findings and perspectives on its cause, as well as offering various solutions to overcome it. Numerous books and works have been written on this subject, but one of the books that has recently been published in this regard is Etiology of Iran’s underdevelopment. The study of the book shows that this work can be criticized from three aspects: form, methodology and content, and the purpose of this research is to clarify the weaknesses and shortcomings of the book in the mentioned domains. All in all, it seems that the book doesn’t have any special innovation and it has not been able to open a new scientific horizon in this field.